Water-Based LiNi0.83Co0.12Mn0.05O2 Electrodes with Excellent Cycling Stability Fabricated Using Unconventional Binders. Issue 4 (1st April 2022) - Radloff, S.; Scurtu, R.-G.; Hölzle, M.; Wohlfahrt-Mehrens, M.
Abstract : Water-based processing of positive Li-ion battery electrodes is becoming increasingly important to enable green and sustainable electrode production. Although already widely established for carbon-based anodes, the water-based coating process still poses challenges if applied to cathode materials containing high contents of nickel. Positive electrodes using Ni-rich cathode materials with areal capacities of 2.6 mAh cm −2 were prepared either with Epoxy, a polyisocyanate-based (ICN) binder or polyacrylic acid (PAA). All three binders can cross-link with Na-carboxymethyl cellulose (CMC) used in the formulation. In bi-layer pouch-cells, such cathodes based on Epoxy or ICN binders reach an excellent long-term 1 C charge/discharge capacity retention of 85% and 88% after 1000 cycles, whereas electrodes with PAA only reach 65%. Post-mortem analysis of cells after cycling suggests aging of the cathode electrode as main source of deactivation. According to scanning electron microscopy data, the aqueous processing does not lead to a stronger cracking of the secondary CAM particles and no enhanced dissolution of transition metals was found on the anode side. However, a stronger increase in charge-transfer impedance is observed for the aged water-based cathodes. Thus, the formation of a blocking surface layer appears to be the major reason for performance deterioration with increasing cycle number.